In-plane uniaxial magnetic anisotropy induced by anisotropic strain relaxation in high lattice-mismatched Dy/Sc superlattices - Benito, L; Ballesteros, C; Ward, R (American Physical Society, 2014)
We report on the magnetic and structural characterization of high lattice-mismatched [Dy2nm/SctSc] superlattices, with variable Sc thickness tSc= 2-6 nm. We find that the characteristic in-plane effective hexagonal magnetic anisotropy K66,ef reverses sign and undergoes a dramatic reduction, attaining values of ≈13-24 kJm-3, when compared to K66=-0.76 MJm-3 in bulk Dy. As a result, the basal plane magnetic anisotropy is dominated by a uniaxial magnetic anisotropy (UMA) unfound in bulk Dy, which amounts to ≈175-142 kJm-3. We attribute the large downsizing in K66,ef to the compression epitaxial strain, which generates a competing sixfold magnetoelastic (MEL) contribution to the magnetocrystalline (strain-free) magnetic anisotropy. Our study proves that the in-plane UMA is caused by the coupling between a giant symmetry-breaking MEL constant Mγ,22≈1 GPa and a morphic orthorhombiclike strain γ,1≈10-4, whose origin resides on the arising of an in-plane anisotropic strain relaxation process of the pseudoepitaxial registry between the nonmagnetic bottom layers in the superstructure. This investigation shows a broader perspective on the crucial role played by epitaxial strains at engineering the magnetic anisotropy in multilayers. © 2014 American Physical Society.